Optimization and evaluation of Lisinopril mucoadhesive sustained release matrix pellets: In-vitro and ex-vivo studies - Modhi F. Alagili; Bushra T. AlQuadeib; Lubna Y. Ashri; Mohamed Abbas Ibrahim (Elsevier, 2023)
Lisinopril (LIS) is antihypertensive drug, classified as a class III drug with high water solubility and low permeability. To overcome the low permeability, 32 factorial designs aimed to formulate LIS as a sustained-release (LIS-SR) matrix pellet by extrusion/spheronization. Matrix pellets were composed of wet mass containing Avicel® and polymeric matrix polymers (sodium alginate (SA) and chitosan (CS)). Evaluation of the effect of two independent variables, matrix-forming units (SA and CS) on mean line torque, on pellet size, dissolution rate after 6 h, and mucoadhesion strength of the pellets were assessed using Statgraphics software. The tested formulations (F1-F9) showed that mean line torque ranged from 1.583 to 0.461 Nm, with LIS content in the LIS-SR pellets ranged from 87.9 to 103%, sizes varied from 1906 to 1404 µm and high percentages of drug released from pellets formulations (68.48 to 74.18 %), while the mean zeta potential value of mucoadhesive range from −17.5 to -22.9 mV.The selection of optimized formulation must have the following desirability: maximum peak torque, maximum pellets' particle size, and minimum % LIS release after 6hr. LIS optimized sustained release pellet formula composed of 2,159 % SA and 0.357 % CS was chosen as optimized formula. It's showed a 1.055 Nm mean line torque was responsible for the increased pellet size to 1830.8 μm with decreased release rate 56.2 % after 6 hr, and −20.33 mV average mucin zeta potential.Ex-vivo mucoadhesion studies revealed that that the optimize formulation, exhibited excellent mucoadhesive properties, after 1 h, about 73% of the pellets were still attached to the mucus membrane. Additionally, ex-vivo permeation determination of LIS from the optimized LIS-SR formulation was found to be significantly higher (1.7-folds) as compared to free LIS.In conclusion: LIS-SR matrix pellets, prepared with an extrusion/spheronization have desirable excellent characteristics in-vitro and ex-vivo sustained-release pellet formulation of LIS-SR was able to sustain the release of LIS for up to 8 h.